De Novo EGFR ‐ALK and EGFR ‐ROS1 Co‐Mutations in NSCLC: Clinical Characteristics, Molecular Profiling, and Treatment Outcomes From a Retrospective Analysis - Lili Shen; Hongyu Deng; Wei Liao; Qiang Gu; Lingling Ma; Qingming Jiang; Kaihua Liu (Cancer Medicine)
ABSTRACT Background De novo epidermal growth factor receptor‐anaplastic lymphoma kinase (EGFR‐ALK) and EGFR‐ROS proto‐oncogene 1 (EGFR‐ROS1) co‐mutations in non‐small‐cell lung cancer (NSCLC), conditions traditionally considered mutually exclusive. We present the first large‑scale analysis of their clinical and genomic profiles. Methods We identified 26 patients with EGFR‐ALK (n = 20) or EGFR‐ROS1 (n = 6) co‐mutations from two institutions and compared them with cohorts of EGFR‐only, ALK‐only, ROS1‐only, and non‐co‐mutated (NC) controls. Additionally, we validated findings in 66 published co‐mutation cases through a literature review (2010–2023). Results The co‐mutation frequencies were 0.36% for EGFR‐ALK and 0.11% for EGFR‐ROS1. EGFR‐ALKco‐mutations were more commonly diagnosed at earlier stages (50.0% stage 0‐II vs. 22.6% in ALK‐only, p = 0.03). Patients with EGFR‐ALK co‐mutations were older than those with ALK‐only mutations (≥ 60 years: 60.0% vs. 24.5% in ALK‐only, p = 0.01), a trend validated in external pooled cases (51.9% vs. 24.5%, p = 0.01). All EGFR‐ROS1cases were never‐smokers and predominantly female (66.7%), a trend consistent with external pooled cases. Co‐mutated tumors were enriched for EGFR exon 19 deletion (19del, 60.0% vs. 42.2% EGFR‐only) and depleted for L858R. Additionally, 80.0% of EGFR‐ALK cases harbored the EML4‐ALKV3. Non‐smokers exhibited superior overall survival (OS) in both cases (internal p = 0.002, external pooled cases p = 0.03). Among 10 advanced‐stage patients with sufficient clinical follow‐up, two had received dual‐targeted TKI therapies. Both patients tolerated dual‐targeted TKI therapies well, with one requiring dose adjustment due to initial toxicity and subsequently achieving an overall survival exceeding 51 months; however, limited sample size precludes definitive conclusions regarding efficacy. Conclusion De novo co‐mutations represent a distinct NSCLC subset with unique clinical and genomic features, and dual‐targeted therapy shows promise as a strategy that warrants evaluation in prospective studies.